The Influence of Gong Waning Music Therapy toward Anxiety in Patients with Acute Coronary Syndrome - Ode Irman; Yosefina Nelista; Yosephina Maria Hawa Keytimu (Faculty of Nursing Universitas Padjadjaran, 2020)
Anxiety becomes a psychological response when there is an attack and becomes a cause to bad treatment of Acute Coronary Syndrome (ACS) patients. Music therapy interventions to reduce anxiety need to be considered because it has no harmful effects. The study aimed to analyze the influence of gong waning music therapy toward anxiety in patients with ACS in Regional Public Hospital of dr. T.C. Hillers Maumere. The research design was quasi experimental with non-equivalent control group design. The sample was 32 patients divided into 2 groups with 16 patients per group taken by using purposive sampling technique. The intervention was implemented in three days. State Trait Anxiety Inventory (STAI) was used as the instrument of the study. The study used paired t-test, independent sample t-test and repeated anova for data analysis. The study showed that experimental group’s trait anxiety and state anxiety were reduced (p 0.000 and 0.001). There was a difference on anxiety in experimental and control group (p 0.043 and 0.049). There was a bigger decrease of anxiety level in experimental group and it was statistically significant (p 0.000). The findings proved to support intervention of traditional music therapy to reduce anxiety. Nurses should not only focus on physical problems and ignore anxiety. It is hoped that nurses can use music therapy as a non-pharmacological adjunct therapy to help reduce anxiety of ACS patients.